The Effect of Discussion Learning on Cognitive Students 'Ability in Teaching Learning Strategies - Nurulwati, Nurulwati; Zulfahmi, Zulfahmi; Susanna, Susanna (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study was to determine whether or not there was an increase in the cognitive abilities of student learning by applying discussion learning to teaching and learning strategies and student responses to the application of discussion learning. The research was carried out in the physics education department that followed the teaching and learning strategies. The population in this study were all students who took the teaching semester strategy V semester 2019 as many as 60 people. While the research sample was 27 students class 01. Sample selection by purposive sampling. The research method used is the Pre Experiment with the design of Pre test and Post test One Group. The results showed that: tcount> ttable means 20.21 > 1.71. This shows an increase in cognitive learning of students who are taught by learning discussion. While the response of students to the learning process of discussion strongly agreed and agreed at 94.06%. In accordance with the criteria of the percentage of student responses, the response to learning discussion is in the range of 76-100% including the very interested category. Students are motivated to learn by learning discussions that practice his thinking skills and critical thinking in conveying the ideas discussed in class and arises self-confidence in expressing ideas and opinions to others.